Clinically significant drug‐drug interaction between tacrolimus and fluconazole in stable renal transplant recipient and literature review. (22nd November 2019) - He, Jiake; Yu, Yang; Yin, Chenglong; Liu, Hailang; Zou, Hua; Ma, Jingsheng; Yang, Wentao; Liu, Ye; Zhong, Lin; Chen, Xijing
Abstract: What is known and objective: Clinical use of fluconazole against fungal infections in renal transplant patients is complicated by the potentially marked and unpredictable drug‐drug interactions (DDIs). We report a case of tacrolimus‐fluconazole DDI in a stable renal transplant recipient and describe the mechanism, magnitude and duration of this DDI through a literature review. Case summary: A 38‐year‐old woman experienced a 9.1‐fold increase in dose‐normalized tacrolimus trough level (trough concentration/weight‐normalized daily dose) and an 87% decrease in weight‐normalized daily dose (daily dose/body weight) in the treatment of documented Candida albicans oesophagitis by fluconazole. After discontinuation of fluconazole for 161 day, a 26% reduction in weight‐normalized daily dose was required to maintain therapeutic exposure. What is new and conclusion: Oral fluconazole has a more significant impact on its drug interactions with tacrolimus than intravenous fluconazole. Gene screening for CYP3A5 6986 A>G and ABCB1 3435 C>T in organ transplant recipients may help in preventing DDI and facilitating tacrolimus dose adjustment. Abstract : The magnitude and duration of tacrolimus‐fluconazole drug‐drug interaction during hospitalization and follow‐up period.